Hubungan antara Kontrol Sosial Orang Tua dengan Perilaku Menikah Muda pada Remaja di Mandahiliang Kenagarian Koto Laweh Kecamatan Lembang Jaya Kabupaten Solok - Voni Widya Rilasti; Jalius Jalius (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2018)
This research is motivated by the many years of young married behavior in adolescents in Mandahiliang Kenagarian Koto Laweh, Lembang Jaya District, Solok Regency. This is caused by social control of parents of young married behavior in adolescents in Mandahiliang Kenagarian Koto Laweh, Lembang Jaya District, Solok Regency. This research also purpose to describe of parents' social control, describe of young married behavior in adolescents, and the relationship between the two variables.This research is a correlational quantitative research using purposive sampling technique. Data collection techniques are questionnaires and data collection tools in the form of statement sheets. Data analysis techniques using the percentage formula and Product Moment. Based on this research, show some indication that (1) parents' social control of adolescents was still low, (2) young married to adolescents are high category, (3) there is a significant relationship between social control of parents and young married behavior.Keywords: Parental Social Control, Young Married Behavior